The road to a low emission society: Costs of interacting climate regulations - Brita Bye; Kevin R. Kaushal; Orvika Rosnes; Karen Turner; Hidemichi Yonezawa (Statistics Norway, Research Department, 2021)
Transportation is one of the main contributors to greenhouse gas emissions. Climate regulations on transportation are often a mix of sector-specific regulations and economy-wide measures (such as emission pricing). In this paper we analyse the effects on economic welfare, abatement costs and emissions of such interacting and partly overlapping climate regulations for private transportation. Our focus is on Norway, a nation where high taxation of conventional fossil-fuelled cars has paved the floor for another pillar of climate policies: promotion of electric vehicles (EVs) in private transport. Our contribution to the literature is two-fold. First, we analyse the costs and impacts of the partly overlapping climate regulations in transportation - the cap on domestic non-ETS emissions and the goal of all new cars for private households being EVs - focussing on the outcome in 2030 in Norway. Second, we respond to an important gap in the literature through a methodological development in economy-wide computable general equilibrium (CGE) approaches for climate policy by introducing EV technologies as an explicit transport equipment choice for private households. We find that, for the case of Norway, combining a specific EV target with policy to cap emissions through a uniform carbon price triples the welfare costs.
Keywords: C68; H23; Q54; Q58; 330; Climate policy; carbon pricing; green transport policies; overlapping regulations; modelling electric vehicles; CGE-model